Effect Of Peer Tutoring On Studentsâ€™ Academic Achievement In Office Technology And Mangement In Nigerian Polytechnics - Ehirheme, Pauline Egberanmwen; Eze, Titus Iloduba (Journal of Vocational Education Studies, 2021)
Students of Office Technology and Management (OTM) in Nigerian polytechnics have consistently performed below expectations both academically and at work. This may be attributed to use of inappropriate instructional method. The need to improve this situation necessitated the research on effects of peer tutoring on studentsâ€™ academic achievement in OTM in Nigerian polytechnics.Â  Using a research question to guide the study, and a null hypothesis was tested at 0.05 level of significance. A non-randomized quasi experimental research design, adopting pre-test; post-test non-equivalent control group design was used. South West Nigeria was the region of the research work with a populace of 503 National Diploma Year II (ND II) OTM students in four federal polytechnics.Â  Using cluster random sampling, a sample of the intact classes of 227 students from two states in the area of the study was drawn. Three OTM experts validated the â€œOffice Technology and Management Achievement Test (OTMAT)â€ 100 items instrument for face and content validity. The Experts input modified some items and cancelled some which reduced 140 test items to 100 used for collecting data. Descriptive statistics of mean was used to analyze data and to respond to the research question while t-test and Analysis of Covariance were used to test the null hypothesis. Kuder-Richardson Formula 21 was adopted to establish internal consistency and reliability of the instrument which yielded a coefficient of 0.86. The research showed that Peer Tutoring Instructional Technique (PTIT) has higher positive effects on studentsâ€™ academic achievement in OTM than Teacher-dominated Instructional Approach (TDIA), thus it can enhance studentsâ€™ academic achievement in OTM. It was, therefore, suggested that OTM lecturers should include the use of Peer Tutoring Instructional Technique to boost learning in teaching their students.